Perancangan SIAKAD Berbasis Web Menggunakan Framework Laravel 10 (Studi Kasus: Jurusan TKJ SMK N 1 Bukittinggi) - M.T, Edryan Sulthan; Okra , Riri Okra; Musril, Hari Antoni; Derta, Sarwo (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to improve the efficiency of data management and academic processes at SMK Negeri 1 Bukittinggi through the implementation of a web-based Academic Information System (SIAKAD). The current academic administrative management is inefficient due to the use of manual systems and outdated data backup methods. Academic processes, especially in communicating students’ grades, are cumbersome and time-consuming. The implementation of SIAKAD is expected to provide accurate, fast, and timely information, as well as enhance the quality of services and the efficiency of academic data management. This study employs the Research and Development (R&D) method to develop and test the feasibility of the product. The system development model used is the System Development Life Cycle (SDLC) with the waterfall model, which emphasizes sequential and analytical stages, flowing from top to bottom like a waterfall. Product testing results show a high level of validity (average score of 0.95) from validation by two experts and excellent practicality (average score of 0.98) based on assessments by two practitioners. The effectiveness test also shows a high level of success (average score of 0.91) based on the kappa formula analysis involving 15 respondents. The web-based academic information system developed using Laravel 10 framework demonstrates excellent performance in speed, responsiveness, and stability. The design of this system successfully resulted in the website http://siakadsmk.uinftik.my.id. The testing results of SIAKAD at the TKJ department of SMK Negeri 1 Bukittinggi indicate an average validity score of 0.95, practicality of 0.98, and effectiveness of 0.91. This application proves to be effective and efficient in managing academic data, facilitating interactions among teachers, students, and administrators, and improving the quality of academic information services at SMK Negeri 1 Bukittinggi.